"Нелинейный томосинтез" как метод решения реконструктивных задач радиационного контроля - Баранов В. А.; Эверт У.; Кулешов В. К. Валерий Константинович; Янушевская М. Н. Марина Николаевна (2011, 2011)
Заглавие с экрана